Eating habits, consumption of ultra-processed foods and their correlation with nutritional status of private schoolchildren (Research, Society and Development, 2020)
The present study aims to evaluate the eating habits, the consumption of ultra - processed foods and their correlation with the nutritional status of students from private schools in Teresina - PI. This is a cross-sectional observational study, a descriptive, exploratory and quantitative field research conducted with 82 children from 7 to 10 years old, of both sexes, in May 2019. The research was approved by the Research Ethics Committee with opinion 3,158,930. Anthropometric data were collected, tabulated in Excel 2016 and analyzed in SPSS (version, 20.0) and analyzed two 24-hour recalls to verify the consumption of ultra-processed foods using Dietbox software. Chi-square test for qualitative variables and Student's t-test for paired samples were used to verify proportional differences between the data, adopting a significance level of p